Load Deflection Properties of Small Diameter Titanium-Niobium-Tantalum-Zirconium Archwire(An In Vitro Study) - Saja I. Alani; Sami K. Al-joubori (Institute of Medico-legal Publications Pvt Ltd, 2022)
Objectives: This study aimed to evaluate the load deflection properties of new niobium-based beta titanium archwire (Gummetal) in comparison with superelasticnickel titanium (SE-NiTi) and copper NiTinickel titanium (Cu-NiTi) archwires. Methods and Material: Gummetal, superelasticNiTiand copper NiTiarchwire segments of 0.014-inch diameter were examined by three point bending test, using Instron testing machine with 10 Newton (N) load cell. Wire segments were tested at 2 and 4 mmdeflections, and at a temperature of 37±1ᵒC. Oneway analysis of variancewas used to compare the means of the groups at a significance of p ˂ 0.05.Results: At 2 mm deflection, the maximum force values and unloading forces of Gummetalwere significantly higher than those of the control (SE-NiTi and Cu-NiTi) archwires. At 4 mm deflection, there was no significant difference between the maximum force values of Gummetal and SENiTiarchwires, however they were significantly higher than those of Cu-NiTiarchwire. Unloading forces of Gummetalarchwire at 4 mmdeflection were initially significantly higher, then became significantly lower than the control wires at 1 mm unloading deflection point.Conclusions: The present study showed that Gummetalarchwirewas less efficient in providing continuous forcesin comparison with SE-NiTi and Cu-NiTiarchwires.Gummetalarchwire cannot be considered superelastic, and its use in the alignment phase may better be limited to mild crowding cases.